Personality Disorder in Thomas Harris "Hanibal Rising" - Runtu, Ferina; Mamentu, Agustin C.; Maukar , Merlin M. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research has the purpose of investigating Antisocial Personality Disorder on the main character of Thomas Harris’ Hannibal Rising which is Hannibal. This research was done qualitatively, indicating the data is not in the form of numbers but rather in the form of words. The data comes from the novel “Hannibal Rising” by Thomas Harris which was written in 2006. In conducting the research, psychodiagnostic analysis was used in order to find out the Antisocial Personality Disorder that Hannibal suffers from. The result of the research showed in characteristics of Antisocial Personality Disorder, that there were 2 signs of being a swindler, 3 signs of manipulating, 11 signs of being aggressive and irritate others, no sign of impulsiveness and 4 signs of lacking of empathy. Furthermore, the result also showed that in the classification of Antisocial Personality Disorder, there were no sign of antisocial jealousy, 2 signs of reputation-defending antisocial, 1 sign of risk-taking antisocial and 4 signs of nomadic antisoocial It can be concluded that Hannibal can be said as a person whom suffer from Antisocial Personality Disorder as his action throughout the novel can be said to indicate the characteristics and classification of Antisocial Personality Disorder.